A superação do trabalho alienado como condição da emancipação humana em Marx - Oliveira, Jorge Luís de (2004)
The issue concerns “human emancipation” in Marx starting from the abolition of the “alienated labor”, in a new productive social order. The objective is to understand and explain the phenomenon of human alienation in the labor process of the capitalist society’s alienated labor and the theoretical and practical conditions of its abolition to achieve the entire man’s emancipation and, thus, the self-development of their human potentialities (their individuality). It was analyzed, then, the theoretical architecture of human emancipation in Marx, explaining some basic categories: alienation (religious and economic), private ownership, labor, labor social division, socialism and communism. The possible nexus among them give us a wider dimension of the “emancipation” problems, focusing the ontological-anthropological character of the matter of man’s social being in its historic transformation context. “Human emancipation” in Marx means, on the one hand, to surpass the social capitalist structure based on the private ownership (of the production means), on the alienated labor and labor social division (iniquitous); and, on the other hand, to inaugurate a communal sociability based on the production’s collective ownership, on the free, creative and active labor and on the “labor conscious organization”, starting from the regulation of an “available time” and a “cooperative productive system”, established by the associated workers. Therefore, the teleology of the emancipation thought in Marx is to retrieve the positive and/or “transcendent” feature of the labor, as exteriorization of the other man’s being (their second nature) or as means of human freedom expression. Man fulfill themselves in the labor in so far as they objectify their essential forces, as a result previously established by the anticipative consciousness of their creative will. Retrieving the generic/universal character of man, as development of their physical and spiritual faculties, is the cabal imperative of realization of the human freedom in Marx. So, the Marxian theoretical axis is the criticism over the bourgeois society, cemented on the antagonism among social classes which dichotomizes the humanity in owners and non-owners, explorers and explored and/or excluded ones, whose discussion surpass its achievements. The Marxian objective is to cause the emergence of the communist sociability in qualitative reproductive bases which aim to fulfill the real and true human necessities, putting an end to the fetishist structure of the capitalist production. The proletarian revolution would be a motor of the new human historic-social development to enter the phase of the freedom kingdom, that is, the communist society; it would be, therefore, the end of the humanity’s prehistory and the beginning of the human true history. Nevertheless, the communism would not be the end of the humanity’s history, but the energetic beginning of the development of a new humanity in which the labor would become the objective expression of man’s creative desires, it would become, then, their first vital necessity. The labor, in this sense, would create the "total man", as Marx said.